Corporate Social Responsibility and Strategic Management: A Bibliometric Analysis - Shirlene Jane Nicole; Suddin Lada; Rudy Ansar; Azaze Azizi Abdul Adis; Lim, Ming Fook; Brahim Chekima (MDPI, 2022)
An organisation should be concerned with more than just profit; it should also be concerned with the social interests and welfare of the surrounding community. In order to ensure that the welfare of society is always safeguarded, the government places a greater emphasis on corporate social responsibility within the business sector. Good corporate social responsibility is only possible in conjunction with strategic management. This study investigated the consistency of previous researchers’ literature reviews on corporate social responsibility and strategic management. A total of 132 Scopus articles were selected for this study, and the article information was analysed utilising the systematic literature review and bibliometric analysis methods.